Testicular ultrasensitive Doppler preliminary experience: a feasibility study. (March 2018) - Rocher, Laurence; Gennisson, Jean-Luc; Ferlicot, Sophie; Criton, Aline; Albiges, Laurence; Izard, Vincent; Bellin, Marie France; Correas, Jean-Michel
Background: Ultrasensitive Doppler is a novel non-invasive ultrasound (US) Doppler technique that improves sensitivity and resolution for the detection of slow flow. Purpose: To investigate the feasibility of ultrasensitive Doppler (USD) for testicular disease diagnosis, using both qualitative and quantitative results. Material and Methods: This prospective study was conducted in 160 successive men referred for scrotal US including B-mode and conventional Color-Doppler. A new USD sequence and algorithm dedicated to academic research were implemented into the US system. The quality criterion for a successful examination was the detection of well delineated intratesticular vessels. Qualitative USD results were described in terms of tumor vascular architecture and flow intensity for different pathologies for 41 patients. The testicular vascularization (TV), defined as a vessel's surface ratio, was quantified using customized MATLAB® software and compared in azoospermic and normal patients. Results: USD was acquired successfully in 153/160 patients (95.6%). The tumor vascular architecture differed depending on the nature of the tumors. Leydig cell tumors exhibited mostly circumferential vascularization, while germ cell tumors exhibited straight vessels through the tumors, or anarchic vascular maps. USD improved the diagnostic performance of testicular Doppler US in a case of incomplete spermatic cord torsion and acute epididymitis. The reproducibility of TV measurements established an interclass correlation of 0.801. Non-Klinefelter syndrome non-obstructive azoospermia patients exhibited a lower TV compared to normal patients, to Klinefelter syndrome, and to obstructive azoospermia patients ( P  < 0.002, P  < 0.005, and P  < 0.05, respectively). Conclusion: Testicular USD can become a promising technique for improving US diagnosis of tumors, acute scrotum, and for determining infertility status.